Network-based technologies for early drug discovery. Issue 3 (March 2018) - Fotis, Chris; Antoranz, Asier; Hatziavramidis, Dimitris; Sakellaropoulos, Theodore; Alexopoulos, Leonidas G.
Graphical abstract: Highlights: The reductionist drug discovery approach entails high attrition rates. Topology-based pathway analysis can unravel the disease mechanism(s). Candidate targets can be prioritized based on their network effects. Pathway-based technologies can help predict a hit's side-effects and efficacy. Abstract : Although the traditional drug discovery approach has led to the development of many successful drugs, the attrition rates remain high. Recent advances in systems-oriented approaches (systems-biology and/or pharmacology) and 'omics technologies has led to a plethora of new computational tools that promise to enable a more-informed and successful implementation of the reductionist, one drug for one target for one disease, approach. These tools, based on biomolecular pathways and interaction networks, offer a systematic approach to unravel the mechanism(s) of a disease and link them to the chemical space and network footprint of a drug. Drug discovery can draw upon this holistic approach to identify the most-promising targets and compounds during the early phases of development.